The innovator's DNA [CD Audio] : mastering the five skills of disruptive innovators - Dyer, Jeff (Brilliance Audio, 2012)
By identifying behaviors of the world's best innovators-- from leaders at Amazon and Apple to those at Google, Skype, and Virgin Group-- the authors outline five discovery skills that distinguish innovative entrepreneurs and executives from ordinary managers.